Plasmodium falciparum Multidrug Resistance-1 (pfmdr1) Gene Mutation in Adults Malaria Patients Attending Murtala Muhammad Specialist Hospital Kano, Northwest Nigeria (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Suspicion of failure in the effectiveness of artemisinin-based combination therapies (currently the ﬁrst-line treatment of malaria, worldwide) is leading to the unofﬁcial use of alternative antimalarials, including chloroquine and sulfadoxine/pyrimethamine in Kano state northwestern Nigeria. To facilitate evidence-based resistance management, antimalarial resistance mutations were investigated in Plasmodium falciparum multidrug resistance-1 (pfmdr1) gene. Hundred adult patients comprising 43 males and 57 females were recruited for the study. The mean age of participants is 36.4 years, minimum and maximum ages were 16 and 60 years respectively, while 41% of them fall within the range of 16 to 30 years. Blood isolates were then analyzed for the presence of malaria parasite using microscopy, the results show a high prevalence of P. falciparum infection in the subject (30%). Pfmdr1 gene, a molecular marker of artemisinin resistance, was successfully sequenced in 21 out of 100 P. falciparum isolates collected from recruited participants. Pfmdr1 mutations were found in 19.5% (4/33) of the samples isolated. The prevalence of the Pfmdr1 N86Y allele was found in 4 samples whilst Y184F and D1246Y were not detected. A total of 4 non-synonymous mutations at codon N86Y were detected. The presence of these mutations highlights the challenges for malaria treatment in Kano state, northwestern Nigeria using antimalarials such as artemether lumefantrine, mefloquine, amodiaquine quinine and lumefantrine.